2016
DOI: 10.5935/abc.20160082
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine to Reduce Atrial Fibrillation in the Postoperative Period of Myocardial Revascularization

Abstract: BackgroundThe high prevalence of atrial fibrillation (AF) in the postoperative period of myocardial revascularization surgery increases morbidity and mortality.ObjectiveTo assess the efficacy of colchicine to prevent AF in the postoperative period of myocardial revascularization surgery, the impact of AF on hospital length of stay and death, and to identify its risk factors.MethodsBetween May 2012 and November 2013, 140 patients submitted to myocardial revascularization surgery were randomized, 69 to the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(66 citation statements)
references
References 15 publications
0
59
0
3
Order By: Relevance
“…[12,23,24] One study also reported the incidence of post-operative infection; although the exact nature of the infections was unspecified. [25]…”
Section: Data Extractionmentioning
confidence: 99%
See 3 more Smart Citations
“…[12,23,24] One study also reported the incidence of post-operative infection; although the exact nature of the infections was unspecified. [25]…”
Section: Data Extractionmentioning
confidence: 99%
“…Six RCTs were reviewed for eligibility and five included. [12,[23][24][25]30] One paper written in Farsi (with an English abstract) was translated using online tools and checked by a cardiologist who was a native Farsi-speaker. Table 1 summarizes study and intervention characteristics of the RCTs.…”
Section: Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Dentre os efeitos farmacológicos que a colchicina desempenha, resultantes da atuação sobre a divisão celular, temos principalmente o efeito anti-inflamatório 3 . Sua diferença para outros medicamentos da mesma classe é que sua pluralidade de ações simultâneas converge em uma implicação mais vigorosa da inativação inflamatória (4)(5) .…”
Section: Introductionunclassified